Corruption and Political Interest: Empirical Evidence at the Micro Level - Benno Torgler; Bin Dong (Center for Research in Economics, Management and the Arts (CREMA), 2008)
In recent years the topic of corruption has attracted a great deal of attention. However, there is still a lack of empirical evidence about the determinants of corruption at the micro level. Therefore we explore in detail the impact of political interest using three different proxies. Furthermore, investigation of the effects of political interest on corruption has been neglected in the present literature. We address this deficiency by analyzing a cross-section of individuals, using the World Values Survey to explore the determinants of corruption using not only perceived corruption as a dependent variable, but also the justifiability of corruption. In addition, we present empirical evidence at both the cross-country level and at the within country level. The results of the multivariate analysis suggest that political interest has an impact on corruption, when controlling for additional significant factors such as institutional conditions (e.g., voice and accountability).
Keywords: K42; D72; O17; J24; 330; Corruption; Political Interest; Social Norms